LANGUAGE MAINTENANCE OF HATA SIMALUNGUN AMONG YOUNG GENERATIONS WITH REFERENCE TO THE GLOBAL CONTEXT - Fitri Sukaisih Saragih; Amrin Saragih; Masitowarni Siregar (LINGUISTICA, 2019)
The research was found on the topic about  Language Maintenance of Hata Simalungun among Young Generations with Reference to the Global Context. This study was conducted by applying descriptive qualitative method. The source of data was taken from the conversations of male and female young generations who live in Kariahan, Kabupaten Simalungun. The technique for analyzing the data is descriptive qualitative research based on Miles, Huberman and Saldana. The result of this research was factors of Hata Simalungun maintenance of young generations in Kariahan Kabupaten Simalungun are Seeing Each Other Frequently, Neighborhood Domain, Ethno Linguistic Vitality and Family Domain (100%), Practice Traditional Ceremony (90%) and Religion Domain (80%). The Ways of Young Generations in maintaining HS are Acquisition the Language (100%), Socially Integrated Population of Active Speakers (80%) and Localities of People Habitually Using the Language (80%). The Reasons of Young Generations Maintain HS are Identity (100%), Prestige or Pride (100%) and Keeping the Language (100%).Keywords: Language Maintenance, Young Generations